2014
DOI: 10.1097/id.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Soft and Hard Tissue Changes Around Laser Microtexture Single Tooth Implants—A Clinical and Radiographic Evaluation

Abstract: The Laser Lok implants showed minimal CBL at 18 months than the commonly accepted 1.5 to 2.0 mm. The periimplant soft tissue stability was maintained throughout the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study. The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study. The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles are RCTs 30 , 31 , 33 and six are cohort studies 27‐29,34‐36 . Six case series 21–26 observing implants with LMS collars without controls were also included to evaluate the overall performances of the LMS design. All articles were published from 2009 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations